2022
DOI: 10.18502/jmehm.v14i19.8179
|View full text |Cite
|
Sign up to set email alerts
|

Compassion-based care for COVID-19 Patients: a qualitative analysis of nurses’ perceptions

Abstract: Compassion is a basic approach to medical practice and is the core component of health care. The purpose of the present study was to explore nurses' perceptions of compassion-based care (CBC) for COVID-19 patients. In this qualitative study, the participants were selected using purposeful sampling. Individual and semi-structured interviews were conducted with 25 nurses, and conventional content analysis was used to categorize the data. In the care of COVID-19 patients, CBC consisted of three categories includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Shin and Yoo ( 2022 ) showed that during COVID‐19 pandemic, there was a close relationship between patients and nurses (Shin & Yoo, 2022 ). According to a study by Ghanbari‐Afra et al ( 2021 ), in Iran, showed that during COVID‐19 pandemic, high workload caused nurses to have a better understanding about patient care, despite enduring many hardships, and there was an atmosphere of friendship, cooperation and sympathy with patients and also colleagues(Ghanbari‐Afra et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shin and Yoo ( 2022 ) showed that during COVID‐19 pandemic, there was a close relationship between patients and nurses (Shin & Yoo, 2022 ). According to a study by Ghanbari‐Afra et al ( 2021 ), in Iran, showed that during COVID‐19 pandemic, high workload caused nurses to have a better understanding about patient care, despite enduring many hardships, and there was an atmosphere of friendship, cooperation and sympathy with patients and also colleagues(Ghanbari‐Afra et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HCWs responded to the COVID-19 pandemic with valuable efforts to address physical, emotional, social, and spiritual needs. In addition, they were able to develop relationships with the patients and their families and support them in dealing with stress and fear [26]. For example, despite the challenges of the COVID-19 pandemic, nurses continued building a nurse-patient relationship through therapeutic communication.…”
Section: Discussionmentioning
confidence: 99%
“…After witnessing the intense suffering of these patients, nurses expressed great concern about their patients' fragility, as their very existence was threatened. Nurses were concerned about their patients' gradual health deterioration, 16,43,44 sense of isolation, 22,24,45 fear of death, 22,23,46 despair of dying alone, 16,[23][24][25]43,47 and the risk of possibly having an indecent funeral. 43,48 Such concerns led nurses to imagine and reflect on how distressed their patients and families must be as the disease progressed.…”
Section: Ambivalent Emotionsmentioning
confidence: 99%